Modeling gating charge and voltage changes in response to charge separation in membrane proteins - Kim, Ilsoo; Chakrabarty, Suman; Brzezinski, Peter; Warshel, Arieh (Proceedings of the National Academy of Sciences of the United States of America, 2014)
Measurements of voltage changes in response to charge separation within membrane proteins can offer fundamental information on mechanisms of charge transport and displacement processes. A recent example is provided by studies of cytochrome c oxidase. However, the interpretation of the observed voltage changes in terms of the number of charge equivalents and transfer distances is far from being trivial or unique. Using continuum approaches to describe the voltage generation may involve significant uncertainties and reliable microscopic simulations are not yet available. Here, we attempt to solve this problem by using a coarse-grained model of membrane proteins, which includes an explicit description of the membrane, the electrolytes, and the electrodes. The model evaluates the gating charges and the electrode potentials (c.f. measured voltage) upon charge transfer within the protein. The accuracy of the model is evaluated by a comparison of measured voltage changes associated with electron and proton transfer in bacterial photosynthetic reaction centers to those calculated using our coarse-grained model. The calculations reproduce the experimental observations and thus indicate that the method is of general use. Interestingly, it is found that charge-separation processes with different spatial directions (but the same distance perpendicular to the membrane) can give similar observed voltage changes, which indicates that caution should be exercised when using simplified interpretation of the relationship between charge displacement and voltage changes.
Keywords: bacterial reaction center; electrogenicity; membrane potential; proton/electron transfer

Molecular dynamics simulation and experimental study on the growth of methane hydrate in presence of methanol and sodium chloride - Choudhary, Nilesh; Kushwaha, Omkar Singh; Bhattacharjee, Gaurav; Chakrabarty, Suman; Kumar, Rajnish (Energy Procedia, 2017)
The plugging of processing and transportation lines by gas hydrate formation is a challenging problem for safe exploitation of oil and gas. The existence of water soluble third component (like methanol and sodium chloride) in the aqueous phase influence the gas hydrate formation thermodynamically also possibly affects the kinetics of hydrate growth. Inorganic salt and organic molecule (alcohols) at high concentration in the aqueous phase have been used as thermodynamic inhibitors to effectively prevent the hydrate formation. This study utilizes molecular dynamics as well as an experimental method to investigate the mechanism of the hydrate formation and the effect of additives. The MD simulation showed that at moderate temperature and pressure, a low concentration (1 wt %) of methanol and NaCl enhances methane hydrate growth kinetics. Significant numbers of methanol molecules were observed inside the gas hydrate cages whereas Na⁺/Cl⁻ ions leach out during hydrate formation.

Molecular view of CO2 capture by polyethylenimine: role of structural and dynamical heterogeneity - Sharma, Pragati; Chakrabarty, Suman; Roy, Sudip; Kumar, Rajnish (Langmuir, 2018)
The molecular thermodynamics and kinetics of CO2 sorption in Polyethylenimine (PEI) melt have been investigated systematically using GCMC and MD simulations. We elucidate presence of significant structural and dynamic heterogeneity associated with the overall absorption process. CO2 adsorption in a PEI membrane shows a distinct two-stage process of a rapid CO2 adsorption at the interfaces (hundreds of picoseconds) followed by a significantly slower diffusion limited release toward the interior bulk regions of PEI melt (hundreds of nanoseconds to microseconds). The spatial heterogeneity of local structural features of the PEI chains lead to significantly heterogeneous absorption characterized by clustering and trapping of CO2 molecules that then lead to subdiffusive motion of CO2. In the complex interplay of interaction and entropy, the latter emerges out to be the major determining factor with significantly higher solubility of CO2 near the interfaces despite having lower density of binding amine groups. Regions having higher free-volume (entropically favorable) viz. interfaces, pores and loops demonstrate higher CO2 capture ability. Various local structural features of PEI conformations, for example, inter- and intrachain loops, pores of different radii, and di- or tricoordinated pores are explored for their effects on the varying CO2 adsorption abilities.

Macro and molecular level insights on gas hydrate growth in the presence of hofmeister salts - Choudhary, Nilesh; Kushwaha, Omkar Singh; Bhattacharjee, Gaurav; Chakrabarty, Suman; Kumar, Rajnish (Industrial & Engineering Chemistry Research, 2020)
The effect of few monovalent salts (NaCl, NH4Cl, and GdmCl) as additives, according to the Hofrneister series on the growth of methane gas hydrates, has been studied using experiments as well as molecular dynamics (MD) simulation. Further, the Hofmeister effects on hydrate crystallization have been correlated with the methanol as an additive, which is a known thermodynamic hydrate inhibitor for hydrate growth. One of the previous studies (discussed later in this article) available in the literature concludes that methane hydrate formation from ice might show enhanced kinetics in the presence of salts; this behavior is contrary to the general usage of such salts as hydrate inhibitors. This conclusion may not necessarily be true for experiments done with liquid water, and therefore, this work explores the behavior of these salts in a lab-scale setup. In addition, current work reports detailed MD simulation studies to gain insight into the mechanism of hydrate formation in the presence of Hofmeister series salts at two different concentrations of 1 and 10 wt % in water and compare the results with hydrate formation in the methanol-water system. Our study suggests that the presence of these additives at low concentrations (1 wt %) does enhance the hydrate growth kinetics. However, at higher concentrations (10 wt %), inhibition by these additives persisted, and prolonged nucleation, as well as retarded growth, was observed.

Morphology and dynamics of self-assembled structures in mixed surfactant systems (SDS plus CAPB) in the context of methane hydrate growth - Hande, Vrushali; Choudhary, Nilesh; Chakrabarty, Suman; Kumar, Rajnish (Journal of Molecular Liquids, 2020)
Presence of small dosages of surfactants in the aqueous phase has been reported to enhance the rate of gas hydrate (clathrate) formation. In this work, using extensive atomistic molecular dynamics (MD) simulations, we have investigated how SDS (surfactant) aggregates in the presence/absence of CAPB (co-surfactant) at ambient conditions (temperature 298 K and pressure 1 bar) and at hydrate forming conditions (temperature 275 K and pressure 50 bar) resulting in altered growth kinetics of methane hydrate. We observe that SDS forms aggregates of different sizes and shapes depending on the thermodynamic condition starting from random distributions of the surfactants. In the presence of the CAPB co-surfactant, tightly packed mixed aggregates are formed. Using various structural order parameters, we demonstrate that shape of the aggregates deviates from spherical as well as cylindrical symmetry. During the aggregation process in presence of methane, the methane molecules get absorbed into the aggregates, enhance the aggregation kinetics and provide structural flexibility to the aggregates. This result is partly in agreement with previous experimental observations that SDS (with or without a co-surfactant) may form micelle-like structures under hydrate forming conditions and that methane gets absorbed by these aggregates leading to enhanced solubility of methane in the aqueous phase. Further, we have investigated the dynamics of shape fluctuations of the aggregates and observed that several distinct relaxation timescales exist in these heterogenous systems. (C) 2020 Elsevier B.V. All rights reserved.